Legal Awareness of Karang Taruna Kampung II Dusun Maju Jaya Regarding Minister of Social Affairs Regulation No. 25 of 2019 - Zainal Arifin; Heri Usmanto; Hendra Hendra (Indonesian Journal of Social Science Education (IJSSE), 2026)
This study aims to analyze the legal awareness of Karang Taruna at the village level regarding Minister of Social Affairs Regulation No. 25 of 2019, highlighting the lack of knowledge and understanding in carrying out the duties of Karang Taruna. As a social organization responsible for developing youth potential and preventing and handling social problems, this organization is a strategic forum for improving local human resources. This study employs a qualitative method with a case study approach, through interviews, observations, and document analysis. The results of the study show that the legal awareness of Karang Taruna Kampung II Dusun Maju Jaya is still relatively low. This organization is not yet aware of the existence of Minister of Social Affairs Regulation No. 25 of 2019, so the guidelines they use as a basis for their organization and for designing and implementing activities are limited to deliberations and activities that are often carried out. Legal awareness encourages entities to understand the law and carry out activities in accordance with it. The implications of this study confirm that legal awareness must continue to be improved, especially among social organizations that play an active role in improving the quality of human resources. Low legal awareness indirectly impacts activities that are less effective and have less of a tangible impact on the surrounding environment, as intended by Minister of Social Affairs Regulation No. 25 of 2019.